Plugging into green growth: towards e-mobility and renewable energy integration in Lao PDR - Dixon, J; Zhou, Z; Phommachanh, S; Kythavone, S; Inthavongsa, P; Hirmer, SA (Elsevier, 2023)
The majority of transport decarbonisation pathways rely on the parallel electrification of the majority of modes of surface transport and significant expansion in renewable electricity generation. Whilst the integration of these two previously siloed sectors – electricity and transport – can benefit the low-carbon transition, there are barriers presenting their realisation. These issues are highly geographically contextual, and little research has been conducted in Lao PDR and the wider Southeast Asia region. To fill this research gap, this paper presents a study of how the barriers to, and enablers for, e-mobility and renewable energy integration in Lao PDR and the wider Southeast Asian region are viewed by different groups of stakeholders. Through engagement with 41 expert stakeholders from a wide range of backgrounds at both the international and national level, we present analysis of the difference in importance assigned to different barriers and enablers. Several differences were identified between how international and country-level stakeholders interpret these issues; generally, international stakeholders identify broad ‘top down’ barriers and enablers whereas country-level stakeholders identify with higher-resolution issues. By bringing their views together, the stakeholder interviews were analysed to support a set of 19 recommendations to international organisations, national governments, financial institutions and the private sector, in fostering e-mobility and renewable energy integration in Lao PDR to support low-carbon growth in the region.